Perspective of beneficial microbes in agriculture under changing climatic scenario: a review - Bhattacharyya, P. N.; Goswami, M. P.; Bhattacharyya, L. H. (Journal of Phytology, 2016)
Agriculture is a complex network of interactions of plants with microorganisms. There is a growing demand for ecologically compatible environment friendly technique in agriculture that might be able to provide adequate supply of nutrients for the increasing human populations through improvement of the quality and quantity of agricultural products. Under the changing climatic scenario of global fluxes of the key biogenic greenhouse gases (CO2, methane and nitrous oxide), and some other environmental problems, the application of beneficial microorganisms in agriculture would serve as an important alternative gateway to some of the traditional agricultural techniques. Microorganisms of agricultural importance represent key ecological strategy for integrated management practices like nutrient management, disease and pest management in order to reduce the use of chemicals in agriculture as well to improve cultivar performance. The present review is intended to focus on the emergence of agriculturally important microorganisms (AIMs) to develop an ideal agricultural system through efficient utilization of nutrients and recycling of energy and thereby to preserve the natural ecosystem resources under climate change. The progress to date in using the beneficial microflora in a variety of applications related to agriculture along with key mechanism of action is also discussed in this review.